Pengaruh Keaktifan Siswa Dalam Organisasi dan Fasilitas Sekolah Terhadap Hasil Belajar Ekonomi Siswa SMA PGRI 2 Denpasar Tahun Pelajaran 2020/2021 - Anggreni, Yesy; Sudana, I Ketut; Jen, Adina; Candra, Ni Nyoman Maika; Suwitra, I Wayan (Jurnal Pendidikan Ekonomi Undiksha, 2022)
The learning process at school provides many experiences for students. Academic and non-academic activities can be obtained at school. Student activity in organizations at school is important to improve students' ability to organize, but if you get too carried away in the organization and forget about learning, it's also not good. This can affect the academic aspects of students. This study aims to determine: 1) The Effect of Student Activity in Organizations on Economic Learning Outcomes of Students at SMA PGRI 2 Denpasar; 2) The Effect of School Facilities on Economic Learning Outcomes of SMA PGRI 2 Denpasar Students; 3) The Effect of Student Activeness in Organizations and School Facilities Together on Economic Learning Outcomes of PGRI 2 Denpasar High School Students. Data were analyzed by statistical analysis of simple regression and multiple regression. Through the prediction results with predictors X1 (Student Activeness in Organizations) and X2 (School Facilities) against Y (Economics Learning Outcomes), the value of Freg is 49.26762. With (N-m-1) in this case db = 93/2, with a significance level of 5%, the Ftable value is 3.09. This means that the regression line analyzed is significant to be used as a basis for prediction because there is a significant relationship between the criteria (Y) and the predictors (X1, X2). Freg is greater than the F table value or 49.26762 > 3.09. So that the null hypothesis tested was rejected and the alternative hypothesis was accepted which indicated that there was a significant relationship between Student Activity in Organizations and School Facilities on Student Economic Learning Outcomes at SMA PGRI 2 Denpasar. Relative Contribution (SR%) for each predictor, namely X1 (Student Activeness in Organizations) = 58.83%, and X2 (School Facilities) = 41.16%. While the regression line is 95.26% which consists of the effective contribution of the X1 predictor (Student Activeness in Organizations) = 56.05%. And the effective contribution of the X2 predictor (School Facilities) = 39.21%. While the remaining 4.74% is influenced by other factors. Based on the results of the analysis and conclusions, it can be suggested to the students to pay attention to the priority scale, time distribution, so that apart from attending class, they can also participate in organizational activities at school.